The position of the America Authorities on the growing activity of the Organization of the Nation of Islam 1930- 1965. - Obaid Naser, Taghreed (Opción, 2019)
The Nation of Islam, one of the religious, social and political organizations that emerged in the United States during the 1930s, was able by its founders to focus on a component that did not receive the attention of the American authorities. On the contrary, it suffered from marginalization and exclusion. In order to achieve its goals and win the members, and adopted the call in prisons and public places and theaters and recreational places taking advan- tage of the annual concerts held by cities, which enabled them to stability and spread, but the follow-up of the US security authorities in various organs and names FBI, The CIA, the police and others, because it was not only a religious organization, but a social, economic and political at the same time, contributed significantly to the obstacles to the organization’s movement and spread, and if it could not prevent them from achieving its goals at the long run.